The Programmer's apprentice - Rich, Charles; Waters, Richard C. (New York, NY : ACM Press, 1990)
This book will give software professional and CASE tool designers a glimpse of what to expect in the future of software development. It will also inspire researchers and students in both artificial intelligence and software engineering by showing the results of synergy between these two disciplines.
1. The Programmer's Apprentice -- 2. Inspection Methods and Cliches -- 3. The Plan Calculus -- 4. Plan Diagrams -- 5. Overlays -- 6. KBEmacs: An Implementation Apprentice -- 7. Implementing a Lisp Program -- 8. Implementing an Ada Program -- 9. Architecture of KBEmacs -- 10. Automated Cliche Recognition -- 11. Requirements and Design -- 12. The Next Generation of CASE.
Includes bibliographical references (pages 215-230).
Keywords: COMPUTER SOFTWARE -- DEVELOPMENT